MODERN THERAPEUTICAL POSSIBILITIES TO SOLVE THE UNITERMINAL EDENTATION - Irina Grădinaru; Daniela-Mariana Calamaz; Raluca-Elena Baciu (Romanian Journal of Medical and Dental Education, 2014)
Introduction Currently, cushioned hinge is one of the recommended solutions for solving mandibular or maxillar uniterminale edentations. Aim of the study This work presents some practical prosthetic possibilities of solving mandibular or maxillar uniterminale edentations. Material and methods The study was conducted on a total of nine patients, aged between 32-48 years, who presented partial uniterminale edentation. To solve uniterminale edentation was used Ancorvis system (damped hinge). Results In all clinical situations solved by using the Ancorvis system was obtain optimal morpho-functional rehabilitation of the stomatognathic system. Conclusions Currently, rehabilitation of uniterminale edentations is possible by using prosthetic appliances that do not affect the marginal periodontium of the remaining teeth. Unilaterale prosthetic appliances with Ancorvis clamping system is successfully used in the terminale edentation therapy. Such prostheses have the advantage of a small gauge, which makes them comfortable. For the success of treatment it is necessary a perfect collaboration between dentist and dental technician.